2017
DOI: 10.1016/j.jsb.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Mutual A domain interactions in the force sensing protein von Willebrand factor

Abstract: The von Willebrand factor (VWF) is a glycoprotein in the blood that plays a central role in hemostasis. Among other functions, VWF is responsible for platelet adhesion at sites of injury via its A1 domain. Its adjacent VWF domain A2 exposes a cleavage site under shear to degrade long VWF fibers in order to prevent thrombosis. Recently, it has been shown that VWF A1/A2 interactions inhibit the binding of platelets to VWF domain A1 in a force-dependent manner prior to A2 cleavage. However, whether and how this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 37 publications
2
40
0
Order By: Relevance
“…In a recent collection of work, binding between the A1 domain in VWF and platelets in blood was explored experimentally; authors of those works presented strong evidence supporting a mechanism for reaction in which the A1 domain could only bind with a platelet if the adjacent A2 domain was sufficiently elongated (11,12). In separate work, it has been instead postulated that flanking residues to A1 undergo some structural change that unmasks A1 and enables binding to platelets (4).…”
Section: Figure 8 (A-f)mentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent collection of work, binding between the A1 domain in VWF and platelets in blood was explored experimentally; authors of those works presented strong evidence supporting a mechanism for reaction in which the A1 domain could only bind with a platelet if the adjacent A2 domain was sufficiently elongated (11,12). In separate work, it has been instead postulated that flanking residues to A1 undergo some structural change that unmasks A1 and enables binding to platelets (4).…”
Section: Figure 8 (A-f)mentioning
confidence: 99%
“…In the works exploring interactions between A1 domains and blood platelets (11,12), it was pointed out that, though elongation of the A2 domain was required for reaction between the two, it was equally important that the A2 domain be not too greatly elongated. The reason is that VWF multimers are subject to scission by the species ADAMTS13 at exposed A2 domains.…”
Section: Figure 8 (A-f)mentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic force micrographs have demonstrated at the single molecule level that under static conditions, vWF assumes a globular conformation, whereas, under high shear flow, vWF turns into an extended chain format [16] that forms ultra-large strings to which platelets bind to initiate clot formation at sites of vascular damage [25] and, when shear stress is above 30.000 s À1 , factor VIII is released from its carrier protein to provide factor VIII to the coagulation cascade [138]. We now realize that, while ultra-large MW (molecular weight) vWF is essential for the normal hemostasis, this multimeric array should not become too large because it alters the thrombotic propensity [15,16,133,134,[138][139][140][141][142][143][144][145][146][147].…”
Section: Vwf/adamts13 Axis In Vascular Health and Diseasementioning
confidence: 99%
“…Although the A2 domain is not directly responsible for vWF/platelet binding, a recent experimental work found that the A2 domain specifically binds to the active conformation of the A1 domain and effectively blocks interactions between the A1 domain and platelet GPIbα [20]. Another work employed both experiments and simulations in tandem and also reported specific A1/A2 domain binding that inhibits vWF/platelet binding; they found that an induced stretching force caused detachment of the two domains, thereby exposing the A1 domain binding site for GPIbα [21]. Clearly then, examination of internal vWF dynamics, namely A2 domain dynamics, is crucial for understanding vWF's role in physiological processes at large.…”
Section: Introductionmentioning
confidence: 99%